Prevalence and Association of Helicobacter Pylori Infection in Bowel Disease at Dr. Cipto Mangunkusumo General National Hospital 2010–2021 - Marcellus Simadibrata; Dewi Mustikarani (The Indonesian Journal of Gastroenterology, Hepatology and Digestive Endoscopy)
BSTRACT[WU1] [DM2]